Step-by-step explanation:
ΔACX is an isosceles triangle, so ∠AXC = ∠XAC. We'll call the measure of this angle x°.
∠AXC and ∠BXC are supplementary, so ∠AXC + ∠BXC = 180. That means ∠BXC = 180 − x.
ΔBXC is an isosceles triangle, so ∠XBC = ∠XCB. We'll call the measure of this angle y°.
Angles of a triangle add up to 180, so:
y + y + (180 − x) = 180
2y = x
y = x/2
∠ACX and ∠XCB are complementary, so ∠ACX + ∠XCB = 90.
x + y = 90
x + x/2 = 90
3/2 x = 90
x = 60
Therefore, ∠AXC = ∠XAC = 60°.
Find the perimeter of the triangle
Answer:
=136
Step-by-step explanation:
Lets solve the triangle using the sine formula.
c/sine C=a/sine A
C= 180-(72+16)
=92°
61/Sin 92=a/sin 72
a=(61 sin 72)/sin 92
=58.0
Solving for b:
c/sin C= b/Sin B
61/sin 92= b/Sin 16
b=(61 Sin 16)/Sin 92
=16.82
Perimeter = 61 +58+ 16.82 = 135.82
Answer =136 to the nearest whole number.
Sidney has 46,880 marbles to put into giant jars. She wants to put the same number of marbles in each jar with no extra marbles. How many jars could Sidney use?
Select all possible numbers:
4 , 2 , 10 , 5
Answer:
4 , 2 , 10 , 5
Step-by-step explanation:
46,880
Since this is an even number, we can divide by 2
46,880/2 =23440
Since this number ends in either a 0 or a 5 we can divide by 5
46880/5 =9376
Since the number is divisible by 2 and 5, we know it is divisible by 10
46880/10 =4688
The only number we need to check is 4
If the last 2 numbers are divisible by 4 then the number is divisible by 4
80/4 = 20 so the number is divisible by 4
46880/4 =11720
46880 is divisible by 4,2,10,5
Answer:
all of the are correct
Please help, it'd be greatly appreciated.
I keep failing this, it's my last resort.
Answer:
the measure of angle 4 should be 45
Step-by-step explanation:
since angle 2 and 4 are congruent, 2x+15 = x + 30
so x = 15
15 + 30 = 45
If f(1) = 160 and f(n + 1) = –2f(n), what is f(4)?
Answer:
-1280
Step-by-step explanation:
There are 2 ways you could do this. You could just do the question until you come to the end of f(4). That is likely the simplest way to do it.
f(1) = 160
f(2) = - 2 * f(1)
f(2) = -2*160
f(2) = -320
f(3) = -2 * f(2)
f(3) = -2 * - 320
f(3) = 640
f(4) = - 2 * f(3)
f(4) = - 2 * 640
f(4) = - 1280
I don't know that you could do this explicitly with any real confidence.
[tex]f(1)=160\\f(n+1)=-2f(n)\\\\f(2)=-2\cdot 160=-320\\f(3)=-2\cdot(-320)=640\\f(4)=-2\cdot 640=-1280[/tex]
Please help me with this question
Answer:
I
Step-by-step explanation:
At least means greater than or equal to
a ≥ 10
That is a closed circle
We have a closed circle at 10
We have to be at least 10 years old
Closed circle at 10, line going to the right
write the equation of a line that goes through point (4,0) and has an undefined slope
x=4
x=0
y=4
y=0
Answer:
x = 4Step-by-step explanation:
A line with undefined slope is a vertical line.
An equation of a vertical line: x = a (a - real number).
Each point on a line x = a has coordinates (a, b) (b - any real number).
We have the point (4, 0) → x = 4
The equation of the line with the following characteristics is: x = 4.
------------
Traditionally, the equation of a line is given by:
[tex]y = mx + b[/tex]
m is the slope.b is the y-intercept.However, if the slope is undefined, there is a vertical line, given by equation:
[tex]x = c[/tex]
In which c is the value of x.In this question, it goes through point (4,0), that is, [tex]c = 4[/tex], and the equation if:
[tex]x = 4[/tex].
A similar problem is given at https://brainly.com/question/15789516
What is the x intercept of
f(x)=(x-7)^2
Answer:
The x-intercept is (7,0).
Step-by-step explanation:
See the graph below for explanation
factor the GCF: 12a^3b + 8a^2b^2 — 20ab^3
Answer:
GCF = 4ab
Step-by-step explanation:
We need to factor the GCF of
12a^3b+8a^2b^2-20ab^3
Finding the common term: 4ab
So, GCF = 4ab
Factoring the common term
12a^3b+8a^2b^2-20ab^3= 4ab(3a^2+2ab-5b^2)
use the formula to find the value of $400 invested in 4%
Answer:
Some part of the question is missing , you are requested to kindly recheck it once. There must be some time provided in the problem
Step-by-step explanation:
The cost, C, to produce b baseball bats per day is modeled by the function C(b) = 0.06b2 – 7.2b + 390. What number of bats should be produced to keep costs at a minimum?
Check the picture below, that's just an example of a parabola opening upwards.
so the cost equation C(b), which is a quadratic with a positive leading term's coefficient, has the graph of a parabola like the one in the picture, so the cost goes down and down and down, reaches the vertex or namely the minimum, and then goes back up.
bearing in mind that the quantity will be on the x-axis and the cost amount is over the y-axis, what are the coordinates of the vertex of this parabola? namely, at what cost for how many bats?
[tex]\bf \textit{vertex of a vertical parabola, using coefficients} \\\\ C(b) = \stackrel{\stackrel{a}{\downarrow }}{0.06}b^2\stackrel{\stackrel{b}{\downarrow }}{-7.2}b\stackrel{\stackrel{c}{\downarrow }}{+390} \qquad \qquad \left(-\cfrac{ b}{2 a}~~~~ ,~~~~ c-\cfrac{ b^2}{4 a}\right)[/tex]
[tex]\bf \left( -\cfrac{-7.2}{2(0.06)}~~,~~390-\cfrac{(-7.2)^2}{4(0.06)} \right)\implies (60~~,~~390-216) \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ ~\hfill (\stackrel{\textit{number of bats}}{60}~~,~~\stackrel{\textit{total cost}}{174})~\hfill[/tex]
To find the number of bats that should be produced to minimize costs, we need to find the minimum point on the cost curve given by the function C(b) = 0.06b^2 - 7.2b + 390. Using the vertex formula, we find that the minimum occurs at b = 60.
Explanation:To find the number of bats that should be produced to keep costs at a minimum, we need to determine the minimum point on the cost curve given by the function C(b) = 0.06b^2 - 7.2b + 390. The minimum point of a quadratic function can be found using the vertex formula: b = -b / (2a), where a is the coefficient of the quadratic term and b is the coefficient of the linear term. In this case, a = 0.06 and b = -7.2. Plugging these values into the formula, we get b = -(-7.2) / (2 * 0.06) = 60.
Therefore, the number of bats that should be produced to keep costs at a minimum is 60.
please help thanks
attachment linked
Answer:
x = 150
D
Step-by-step explanation:
1 / tan(90 - x) = -√3/3 Cross multiply
3 = -√3 * tan(90 - x) Divide by -√3
3/-√3 = tan(90 - x) Rationalize the denominator
3 * √3 / (- √3 * √3 ) =tan(90-x)
3 * √3 / - 3 = tan(90 - x) Divide
- √3 = tan(90 - x) Take the inverse tan of -√3
tan-1(-√3) = 90 - x
-60 = 90 - x Add x to both sides.
x - 60 = 90 Add 60 to both sides
x = 150
What’s x-2 = 3x-84
I just need this answered to be able to answer another equation.
30 points
Answer: x = 41
Step-by-step explanation: You need to isolate x. First, subtract x from each side. You will get:
-2 = 2x - 84
Next, add 84 to each side.
82 = 2x
Divide by 2 on each side.
X = 41
Answer:41
Step-by-step explanation:x-3x=-84+2
-2x=-82
X=-82/-2
X=41
Two events are disjointed. Find P(A or B), if P(A) = 1/7
and P(B) = 3/7.
1/7
3/7
4/7
2/7
Answer:
4/7
Step-by-step explanation:
P(A or B) when A and B are disjointed is P(A)+P(B)
P(A or B)=P(A)+P(B)
P(A or B)=1/7 +3/7
P(A or B)=4/7
The value of P(A or B) is 4/7 (3rd option)
What is the formula of P(A or B) of disjoint events ?Let A and B be two disjoint events.
Then, probability of A is P(A) & probability of B is P(B).
In this case, the probability of A or B is the sum of P(A) & P(B)
∴ P(A or B) = P(A) + P(B)
What is the required probability ?Given, P(A) = 1/7 & P(B) = 3/7
So, P(A or B) = P(A) + P(B)
= 1/7 + 3/7
= (1+3)/7
= 4/7
Required value of P(A or B) is 4/7
Learn more about disjoint events here :
https://brainly.com/question/8639736
#SPJ2
If you buy a car for 15500 an average on an average a new car loses 11% of its value the moment that is driven off the lot once you driving the car back to your new car off the lot what is the value be
Answer:
$13,795
Step-by-step explanation:
15500/x=100/11
(15500/x)*x=(100/11)*x - we multiply both sides of the equation by x
15500=9.0909090909091*x - we divide both sides of the equation by (9.0909090909091) to get x
15500/9.0909090909091=x
1705=x
x=1705
now we have:
11% of 15500=1705
Which polynomial function has a leading coefficient of 1, roots –2 and 7 with multiplicity 1, and root 5 with multiplicity 2?
Answer:
Answer in factored form: [tex]P(x)=(x+2)(x-7)(x-5)^2[/tex]
Answer in standard form: [tex]P(x)=x^4-15x^3+61x^2+15x-350[/tex]
Step-by-step explanation:
I don't see your choices but I can still give you a polynomial fitting your criteria. I will give the answer in both factored form and standard form.
The following results are by factor theorem:
So if x=-2 is a zero then x+2 is a factor.
If x=7 is a zero then x-7 is a factor.
If x=5 is a zero then x-5 is a factor. It says we have this factor twice. I know this because it says with multiplicity 2.
So let's put this together. The factored form of the polynomial is
A(x+2)(x-7)(x-5)(x-5)
or
[tex]A(x+2)(x-7)(x-5)^2[/tex]
Now A can be any number satisfying a polynomial with zeros -2 and 7 with multiplicity 1, and 5 with multiplicity 5.
However, it does say we are looking for a polynomial function with leading coefficient 1 which means A=1.
[tex](x+2)(x-7)(x-5)^2[/tex]
Now the factored form is easy.
The standard form requires more work (multiplying to be exact).
I'm going to multiply (x+2)(x-7) using foil.
First: x(x)=x^2
Outer: x(-7)=-7x
Inner: 2(x)=2x
Last: 2(-7)=-14
--------------------Adding.
[tex]x^2-5x-14[/tex]
I'm going to multiply [tex](x-5)^2[/tex] using formula [tex](u+v)^2=u^2+2uv+v^2[/tex].
[tex](x-5)^2=x^2-10x+25[/tex].
So now we have to multiply these products.
That is we need to do:
[tex](x^2-5x-14)(x^2-10x+25)[/tex]
I'm going to distribute every term in the first ( ) to
every term in the second ( ).
[tex]x^2(x^2-10x+25)[/tex]
[tex]+-5x(x^2-10x+25)[/tex]
[tex]+-14(x^2-10x+25)[/tex]
------------------------------------------ Distributing:
[tex]x^4-10x^3+25x^2[/tex]
[tex]+-5x^3+50x^2-125x[/tex]
[tex]+-14x^2+140x-350[/tex]
-------------------------------------------Adding like terms:
[tex]x^4-15x^3+61x^2+15x-350[/tex]
Answer:
f(x) = (x – 7)(x – 5)(x – 5)(x + 2)
Step-by-step explanation:
Use the graph representing bacteria decay to estimate the domain of the function and solve for the average rate of change across the domain
,
A.
[tex]0 \leqslant y \leqslant 80, - 0.6875[/tex]
B.
[tex]0 \leqslant y \leqslant 80, - 1.45[/tex]
C.
[tex]0 \leqslant x \leqslant 55, - 1.45[/tex]
D.
[tex]0 \leqslant x \leqslant 55, - 0.6875[/tex]
Answer:
C. [tex]0\le x\le55,-1.45[/tex]
Step-by-step explanation:
The domain of the function refers to all values of x for which the function is defined.
From the diagram the graph of the function exist on the interval [tex]x=0[/tex] to [tex]x=55[/tex].
The average rate of change is the slope of the secant line joining the points (0,f(0)) and (55,f(55)).
The average rate of change of this function f(x) on this interval is
[tex]\frac{f(55)-f(0)}{55-0}[/tex]
From the graph, [tex]f(0)=80[/tex] and [tex]f(55)=0[/tex].
The average rate of change becomes:
[tex]\frac{0-80}{55-0}=\frac{-80}{55}=-1.45[/tex] to the nearest hundredth.
The correct answer is: C
Answer: The correct answer would be C
Step-by-step explanation:
I need help with this
Answer:
ƒ(x) = (x - 1)(x - 2)(x - 3)
Step-by-step explanation:
The graph shown is that of a cubic equation with zeros at x = 1, 2, and 3
The function in factored form must be
ƒ(x) = (x - 1)(x - 2)(x - 3).
When you solve for the zeros, the sign of the constant changes. For example
x - 1 = 0
x = 1
find the slope and the y-intercept of the line 7x-2y=-8
Answer:
slope = 7/2
y-int = 4
Step-by-step explanation:
parent formula is y=mx+b ; where m is slope and b is y-int.
begin by rewriting formula to isolate y ; 7x+8=2y ; divide bothe sides by 2 ; so
7/2 x+4=y. slope/m=7/2 and y-int/b=4
Factor completely. X^3+6x+x^2+6
Answer:
(x+1) (x^2+6)
Step-by-step explanation:
x^3+6x+x^2+6
Rearranging the order
x^3+x^2 + 6x+6
We can factor by grouping
Taking an x^2 from the first two terms and a 6 from the last two terms
x^2(x+1) +6(x+1)
Now we can factor out an (x+1)
(x+1) (x^2+6)
Identify the zeros of f(x) = (x + 1)(x − 8)(5x + 2).
1, 2 over 5, 8
−1, −2 over 5,−8
−1, 2 over 5, −8
−1, −2 over 5,8
Answer:
The zero's are -1, -2/5, 8
Step-by-step explanation:
f(x) = (x + 1)(x − 8)(5x + 2)
We can use the zero product property
0 = (x + 1)(x − 8)(5x + 2)
0 = x+1 0 = x-8 0 =5x+2
x=-1 x=8 -2 =5x
x=-1 x=8 -2/5 =x
The zero's are -1, -2/5, 8
multiply (2x^2 + 3x - 6)(x - 1)
Answer:
2x^3 + x^2 - 9x + 6
Step-by-step explanation:
(2x^2 + 3x - 6)(x - 1)
2x^3 + 3x^2 - 6x - 2x^2 - 3x + 6
2x^3 + x^2 - 9x + 6
SOS I need help with this question
Equation: 2x^2 + 10x - 3x - 15
Step1: Factor completely (10 points)
step2: after the polynomial is factored, solve the zeroes of the function
step3: describe the end behavior of the graph
step4: will the vertex of the function be minimum or maximum function?
Answer:
1) (2x - 3)(x + 5)
2) 1.5, -5
3) Open upwards from both ends
4) Minimum
Step-by-step explanation:
Step 1:
The given polynomial is:
[tex]2x^{2}+10x-3x-15[/tex]
Taking out commons, we get:
[tex]2x(x+5)-3(x+5)\\\\ =(2x-3)(x+5)[/tex]
This is the factorized form of the polynomial.
Step 2:
The zeros of the functions occur when the function is equal to zero.
i.e.
[tex](2x-3)(x+5)=0\\\\ \text{According to the zero product property}\\\\ 2x-3=0, x+5=0\\\\ x =\frac{3}{2}=1.5, x = -5[/tex]
This means, the zeros of the polynomial are 1.5 and -5
Step 3:
The end behavior of a graph depends on its degree and the sign of leading coefficient. Since the degree is even and the coefficient is positive the graph of the polynomial will opens upwards from left and right side.
Step 4:
The given polynomial is a quadratic function with positive leading coefficient. Since it open vertically upwards, its vertex will be the lowest most point. So, the vertex will be the minimum of the function.
-42.8451
Round the result to the nearest tenth and then to the nearest hundredth
Answer:
Tenth:-42.8
Hundredth: -42.85
To explain:
To the right of the decimal point every name of the place ends with -th.
If a number is bigger than 5 you round the number left to it by 1
If it's 4 or smaller you don't do anything.
In a population of 1000 individuals, 100 new individuals were born and 200
individuals died over the course of 1 year. Which equation shows how to
calculate the population growth rate of this population?
O
A. 0.10 0.20 = 0.02
O
B. 0.10 - 0.20 = -0.10
O
C. 0.20 +0.10 = 0.30
O
D. 0.20 - 0.10 = 0.10
Answer:
the answer to this question is b.
Answer:
The correct option is B.
Step-by-step explanation:
It is given that In a population of 1000 individuals, 100 new individuals were born and 200 individuals died over the course of 1 year.
We need to find the population growth rate of this population.
Rate of birth = [tex]\frac{100}{1000}=0.10[/tex]
Rate of death = [tex]\frac{200}{1000}=0.20[/tex]
The formula for rate of change is
Rate of change = Rate of birth - Rate of death
Rate of change = 0.10 - 0.20
Rate of change = -0.10
The required equation is 0.10 - 0.20 = -0.10.
Therefore, the correct option is B.
What is the factored form of 3x+24y?
Both 3 and 24 have 3 in common. This means that you can factor a three out of this equation like so:
3(x + 8y)
If you distribute the three back into the equation then you would then get 3x + 24y (the equation before factoring)
Hope this helped!
~Just a girl in love with Shawn Mendes
Answer:
3 ( x + 8 y )
Step-by-step explanation:
Since 3 is the LCM ( lowest common multiple ) which goes into both numbers, it will go on the outside of the brackets. To get the insides of the brackets you have to divide the original expression by 3
3 ÷ 3 x = x
24 y ÷ 3 = 8 y
And our final factored form is 3 ( x + 8 y )
the slope of the line below is -4. write the equation of the line in point slope form using the coordinates of the labeled point.
Answer:
y-2=-4(x-1)
Step-by-step explanation:
point slope form is written as y-y1=m(x-x1). y1 and x1 are both the coordinates on the line. x1 is the x coordinate y1 is y coordinate. m is the slope.
There are 86,400 frames of animation in 1 hour of anime. How many frames are there per second? There are 3600 seconds in 1 hour. (PLZZ HELP!)
Answer:
There are 86,400 / 3,600 = 24 frames/second
Step-by-step explanation:
Since there are 60 minutes in an hour and 60 seconds in a minute, in an hour you have 60 x 60 = 3,600 seconds.
You have 86,400 frames of animation in 1 hour.
Divide 86,400 by 3,600 to get the number of frames per second.
There are 86,400 / 3,600 = 24 frames/second
To solve, make a simple equation.
86400/3600=x
In order to get x, divide 86400 by 3600 and which x will be 24.
You can either divide the long way or the short way.
Algorithm, mental.
Get rid of the two 0s.
Then you'll get 864/36. .... 24... x=24
So 24 is the answer.
Hope this helps:)
what is 10.15384615 as a fraction?
Answer:
The answer is an attachment I hope it helps!!!
What is the vertex of the graph of the function below?
y= x^2 - 8x+ 12
O A. (2,0)
O B. (4,0)
O C. (2,-4)
O D. (4,-4)
Answer:
D. (4, -4)
Step-by-step explanation:
Convert to vertex form by completing the square.
For a polynomial y = x² + bx + c, first add and subtract (b/2)² to the polynomial. Then factor.
Here, b = -8. So (b/2)² = (-8/2)² = 16.
y = x² − 8x + 12
y = x²− 8x + 16 − 16 + 12
y = (x − 4)² − 16 + 12
y = (x − 4)² − 4
The vertex is (4, -4).
The vertex of the function y = x2 - 8x + 12 is found by first using the formula -b/2a to find the x-coordinate of the vertex, and then substituting that value into the equation to find the y-coordinate. This results in the vertex being at the point (4,-4).
Explanation:The vertex of a quadratic function given in the form y = ax2 + bx + c is found using the formula -b/(2a) for the x-coordinate, and substituting that value into the equation to find the y-coordinate. In the given function y = x2 - 8x + 12, a is equal to 1, and b is equal to -8.
Using the vertex form, the x-coordinate of the vertex can be found by using -b/2a, or --8/(2*1), which equals 4. This becomes the x-coordinate of our vertex. Substituting x = 4 into our equation, we find y = (4)2 - 8*4 + 12 = -4. Therefore, the vertex of the given graph is at the point (4,-4), which corresponds to option D.
Learn more about Vertex of Quadratic Function here:https://brainly.com/question/31410496
#SPJ2
Find volume of rectangular prism length(4x+3) width (x-6) height (2x-1)
Answer:
8x^3-46x^2-5x+18
Step-by-step explanation:
The volume of a rectangular prism is L*W*H where
L=length
W=width
H=height.
So we want to probably find the standard form of this multiplication because writing (4x+3)(x-6)(2x-1) is too easy.
Let's multiply (4x+3) and (x-6), then take that result and multiply it to (2x-1).
(4x+3)(x-6)
I'm going to use FOIL here.
First: 4x(x)=4x^2
Outer: 4x(-6)=-24x
Inner: 3(x)=3x
Last: 3(-6)=-18
---------------------------Add.
4x^2-21x-18
So we now have to multiply (4x^2-21x-18) and (2x-1).
We will not be able to use FOIL here because we are not doing a binomial times a binomial.
We can still use distributive property though.
(4x^2-21x-18)(2x-1)
=
4x^2(2x-1)-21x(2x-1)-18(2x-1)
=
8x^3-4x^2-42x^2+21x-36x+18
Now the like terms are actually already paired up we just need to combine them:
8x^3-46x^2-5x+18
Answer:
[tex]\large\boxed{8x^3-46x^2-15x+18}[/tex]
Step-by-step explanation:
The formula of a volume of a rectangular prism:
[tex]V=lwh[/tex]
l - length
w - width
h - height
We have l = 4x + 3, w = x - 6 and h = 2x - 1.
Substitute:
[tex]V=(4x+3)(x-6)(2x-1)[/tex]
use FOIL: (a + b)(c + d)
[tex]V=\bigg[(4x)(x)+(4x)(-6)+(3)(x)+(3)(-6)\bigg](2x-1)\\\\=(4x^2-24x+3x-18)(2x-1)\qquad\text{combine like terms}\\\\=(4x^2-21x-18)(2x-1)[/tex]
use the distributive property: a(b + c) = ab + ac
[tex]V=(4x^2-21x-18)(2x)+(4x^2-21x-18)(-1)\\\\=(4x^2)(2x)+(-21x)(2x)+(-18)(2x)+(4x^2)(-1)+(-21x)(-1)+(-18)(-1)\\\\=8x^3-42x^2-36x-4x^2+21x+18[/tex]
combine like terms
[tex]V=8x^3+(-42x^2-4x^2)+(-36x+21x)+18\\\\=8x^3-46x^2-15x+18[/tex]